1987
DOI: 10.1103/physrevlett.59.2792
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Direct Multiquantum Vibrational Excitation in Gas-Surface Scattering: NH3on Au(111)

Abstract: Vibrationally excited NH3 molecules are observed in the scattering of NH3 (v ~0) from Au(lll). We observe up to three quanta of vibrational excitation in the vi ''umbrella'' vibrational mode of NH3. The vibrational excitation probability scales linearly with the kinetic energy of the incident beam above a threshold energy corresponding to the quanta excited, and is independent of the surface temperature, T s , over the range 300 K< T s < 800 K. These results are discussed in terms of an electronically adiabati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 26 publications
1
56
1
Order By: Relevance
“…Vibrational excitation or de-excitation of gas molecules may result in surface phonon destruction or creation and/or electronic de-excitation or excitation. [10][11][12][13][14][15] Vibrational motion of the gas molecules may influence trapping, 14,16 exhibit isotope dependent effects, 17,18 and play a vital role in vibrationally promoted surface reactions, 14,19,20 electron transfer, 21 and even electron emission. 22 Much effort has been devoted to the study of electronically nonadiabatic influences in vibrational energy transfer at solid surfaces, but this has been accomplished for only a few molecule-surface systems.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational excitation or de-excitation of gas molecules may result in surface phonon destruction or creation and/or electronic de-excitation or excitation. [10][11][12][13][14][15] Vibrational motion of the gas molecules may influence trapping, 14,16 exhibit isotope dependent effects, 17,18 and play a vital role in vibrationally promoted surface reactions, 14,19,20 electron transfer, 21 and even electron emission. 22 Much effort has been devoted to the study of electronically nonadiabatic influences in vibrational energy transfer at solid surfaces, but this has been accomplished for only a few molecule-surface systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For example, Kay and co-workers 4 have shown that the vibrational excitation probability of NH 3 (umbrella mode) scattered from a Au(111) surface increases monotonically with the translational incidence energy (E i ) above a threshold close to the vibrational excitation energy. The surface temperature (T s ) had no influence on the vibrational excitation probability.…”
Section: Introductionmentioning
confidence: 99%
“…1 has been previously recognized as a signature of an electronically non-adiabatic energy transfer mediated by free electrons in the metal surface. 1,18,19,21 However, a complete interpretation of the physical meaning of the Arrhenius parameters derived from experiment has been lacking.…”
Section: Comments On Ref 17mentioning
confidence: 99%